1998
DOI: 10.1111/j.1398-9995.1998.tb03884.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of allergy in children in relation to prior BCG vaccination and infection with atypical mycobacteria

Abstract: By influence on the Th1/Th2 cell balance, infectious agents may affect the development of atopic allergy. In this study, we investigated whether previous BCG vaccination or infection with atypical mycobacteria might be related to the development of atopic disease. The study, which involved skin testing with mycobacteria and answers to a questionnaire for more than 6000 children in Sweden, revealed a low prevalence of allergy among BCG-vaccinated children who were immigrants or adopted from other countries. Vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
131
5
3

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 32 publications
(31 reference statements)
7
131
5
3
Order By: Relevance
“…For example, a suggested relationship between the exposure to tuberculosis and a low prevalence of allergy was based on the observation that allergic individuals less often had strongly positive tuberculin reactions, as compared with non-allergic persons (Shirakawa et al 1997). However, this observation is more likely to be due to the fact that atopic individuals have depressed cell-mediated immune responses, including delayed-type hypersensitivity (Strannegård et al 1998). When smaller tuberculin reactions were included in the comparisons, the atopic and non-atopic individuals had a similar prevalence of tuberculin positivity.…”
Section: The Role Of Microbesmentioning
confidence: 97%
“…For example, a suggested relationship between the exposure to tuberculosis and a low prevalence of allergy was based on the observation that allergic individuals less often had strongly positive tuberculin reactions, as compared with non-allergic persons (Shirakawa et al 1997). However, this observation is more likely to be due to the fact that atopic individuals have depressed cell-mediated immune responses, including delayed-type hypersensitivity (Strannegård et al 1998). When smaller tuberculin reactions were included in the comparisons, the atopic and non-atopic individuals had a similar prevalence of tuberculin positivity.…”
Section: The Role Of Microbesmentioning
confidence: 97%
“…However, not all studies have found an inverse association between infections and atopy, but few, in contrast, found a positive or no association (82-86) ( Table 2). These studies, which have obtained data on infections using questionnaires or medical records, but have not, with one exception, used serological testing, have examined the role of measles (83), mycobacteria (86) or several viral and bacterial pathogens (82,84,85). The measles study has been criticized for a selection bias: differential misclassification of exposure has been proposed to explain the possible association found in that study, most probably because of underdiagnosis of measles particularly among healthy nonatopic children (87).…”
Section: Exposure To Bacterial Viral and Protozoan Pathogensmentioning
confidence: 99%
“…1 Although hereditary factors are important for the risk of developing allergic disorders, the increase in prevalence observed in recent years 2 , 3 suggests that non-hereditary risk factors must play a substantial part. Immunological data show that different infections can either promote atopy (respiratory syncytial virus infections) 4 or inhibit atopy (measles, hepatitis A, tuberculosis), 5 , 6 , 7 A change in childhood infectious diseases, vaccination programmes, or both could partly explain this increase, although studies in Sweden, 8 , 9 did not show that BCG vaccination protected against atopy.…”
Section: Introductionmentioning
confidence: 99%